2018
DOI: 10.1038/s41467-018-07207-9
|View full text |Cite
|
Sign up to set email alerts
|

MAIT cells contribute to protection against lethal influenza infection in vivo

Abstract: Mucosal associated invariant T (MAIT) cells are evolutionarily-conserved, innate-like lymphocytes which are abundant in human lungs and can contribute to protection against pulmonary bacterial infection. MAIT cells are also activated during human viral infections, yet it remains unknown whether MAIT cells play a significant protective or even detrimental role during viral infections in vivo. Using murine experimental challenge with two strains of influenza A virus, we show that MAIT cells accumulate and are ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
192
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 168 publications
(200 citation statements)
references
References 49 publications
5
192
3
Order By: Relevance
“…In our study, we looked at early events following IAV infection of PBMCs and showed that IAV can weakly activate and induce degranulation of MAIT cells in as little as 6 hours, and that this was mediated by T1-IFNs. In mice, MAIT cells have previously been shown to rapidly upregulate CD69, CD25, and granzyme B during influenza challenge; T1-IFN signalling was shown to be required for the expression of CD25 on MAIT cells (Wilgenburg et al, 2018). In an in vitro HCV infection model, neutralizing T1-IFNs with B18R significantly reduced CD69 expression and production of IFNγ and granzyme B by MAIT cells, suggesting T1-IFN co-operate with cytokines such as IL-12 and IL-18 during viral infection (van Wilgenburg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we looked at early events following IAV infection of PBMCs and showed that IAV can weakly activate and induce degranulation of MAIT cells in as little as 6 hours, and that this was mediated by T1-IFNs. In mice, MAIT cells have previously been shown to rapidly upregulate CD69, CD25, and granzyme B during influenza challenge; T1-IFN signalling was shown to be required for the expression of CD25 on MAIT cells (Wilgenburg et al, 2018). In an in vitro HCV infection model, neutralizing T1-IFNs with B18R significantly reduced CD69 expression and production of IFNγ and granzyme B by MAIT cells, suggesting T1-IFN co-operate with cytokines such as IL-12 and IL-18 during viral infection (van Wilgenburg et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The exact effector functions expressed depend upon the mode of activation (Hinks et al, 2018; Lamichhane et al, 2019; Leng et al, 2018). Many in vivo studies have established an important role for MAIT cells in protection against bacterial infections (Chua et al, 2012; Georgel, Radosavljevic, Macquin, & Bahram, 2011; Meierovics, Yankelevich, & Cowley, 2013; Wang et al, 2018) and more recently against viruses (Wilgenburg et al, 2018). Therefore, MAIT cells are an important innate-like T cells that bridge the innate and adaptive arms of the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAIT cells comprise a large proportion of these CD161-expressing T cells, and have previously been described to show limited responses to conventional TCR signals although combinatorial signalling can markedly augment this in vitro and also in vivo (Slichter et al, 2016;Turtle et al, 2015)(see also accompanying paper by Hinks and colleagues ). On the other hand, MAIT cells can respond in a fully TCR-independent manner, via cytokine signalling, and such behaviour can also trigger protection in vivo (Wilgenburg et al, 2018). The functional consequences of TCR-dependent vs TCR-independent activation of MAIT cells have not been fully defined -thus to further dissect the differential signals that promote and sustain MAIT cell effector function, is of central importance in defining the role of MAIT cells in both health and disease.…”
Section: Cd161-expressing Human T Lymphocytes Possess Shared Transcrimentioning
confidence: 99%
“…Cytokine-stimulated CD161 ++ CD8 + T cells, including MAIT cells, may exert effector functions by secretion of cytokines and upregulation of Granzyme (Gr)B (Billerbeck et al, 2010;Kurioka et al, 2014). We and others recently highlighted a role for MAIT cells in viral infections, where MAIT cell activation was TCR-independent, but dependent on IL-18 in synergy with IL-12, IL-15, and/or type I interferons (IFN-α/β) (Loh et al, 2016;Wilgenburg et al, 2016), with a critical protective role in vivo (Wilgenburg et al, 2018). Thus it is clear that MAIT cells can be activated via TCRdependent and -independent pathways.…”
Section: Introductionmentioning
confidence: 99%